2017
DOI: 10.3390/ani7120089
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Citizens: Expectations Regarding Dairy Cattle Welfare and Awareness of Contentious Practices

Abstract: Simple SummaryAnimal welfare is an important issue for citizens in North America and Europe, but much less is known about how citizens from emergent countries, such as Brazil, view this topic. Our aim was to explore attitudes of urban Brazilian citizens about dairy production and, in particular, how they view four routine husbandry practices: early cow-calf separation; zero-grazing; culling of the newborn male calf; and dehorning without pain mitigation. Through in-depth interviews and a questionnaire using op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…Participants’ concerns with hens’ natural feeding, and their stated preference for feed containing no hormones, antibiotics or other chemicals is frequently reported, and as in our survey appear to be linked with the desire to consume safe, healthy products, and to avoid food that poses real or perceived risks to human health, to animal integrity and to the environment [ 17 , 19 , 23 , 24 , 44 ]. Perceived associations between natural production systems, hen welfare and egg quality were observed in this and in other surveys [ 32 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants’ concerns with hens’ natural feeding, and their stated preference for feed containing no hormones, antibiotics or other chemicals is frequently reported, and as in our survey appear to be linked with the desire to consume safe, healthy products, and to avoid food that poses real or perceived risks to human health, to animal integrity and to the environment [ 17 , 19 , 23 , 24 , 44 ]. Perceived associations between natural production systems, hen welfare and egg quality were observed in this and in other surveys [ 32 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived associations between natural production systems, hen welfare and egg quality were observed in this and in other surveys [ 32 , 37 ]. Consumers’ belief in these relationships has also been described for other food animal products [ 23 , 42 ], and may explain why naturalness is central to the public acceptability of production systems [ 17 ]. In disconnect with public preferences, and growing international calls for prudent use of antibiotics in animal production [ 45 ], industry stakeholders in Brazil defend the use of antibiotics as growth promoters or for prophylactic use as essential to achieve the production and economic goals of the industry (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellingsen et al, (2014) had revealed that male calves were fed by less quality and insufficient quantity of colostrum supplement by farmers and easily vulnerable to diseases compared to females as they do not receive proper care and medical attention (Renaud et al, 2018). In addition, other risk factors were also found such as culling the -male calf (Cardoso et al, 2017), selling them for veal at 2 nd and 4 th week after birth (Marcé et al, 2011) and prevalence of high mortality rate (Pritchard et al, 2008). Compared to them welfare and ethical consideration of Sri Lankan farmers towards male calves were comparatively high.…”
Section: The Fate Of Male Calvesmentioning
confidence: 99%
“…One last, and increasingly important, aspect to be considered is the societal acceptance of dairy farming. Recent research shows that the welfare of dairy cattle is an important issue for civil society and that some common practices, once widely known, are not easily accepted by the general public (e.g., lack of access to pasture, early cow-calf separation, and disbudding or dehorning without pain relief [49][50][51]). All this should be done keeping in mind that the concept of sustainability is evolving.…”
Section: Discussionmentioning
confidence: 99%